Fabrication of magnetic molecularly imprinted polymer-based covalent–noncovalent synergistic imprinting strategies for the highly specific enrichment of luteolin from honeysuckle - Zhang, Liping; Hao, Peizhi; He, Yifan; Li, Shujing; Li, Tian; Wang, Lan; He, Suna (Frontiers in Sustainable Food Systems, 2024)
Introduction Luteolin (LTL) is the primary active ingredient in honeysuckle, which exhibited wide pharmacological activities, including heat-clearing, detoxifying, anti-inflammatory and anti-oxidant effects. The conventional method for the extraction of LTL consumed a substantial amount of time and organic solvents, and poor selectivity. Therefore, fabrication of novel material with simple preparation process, low cost and excellent selectivity is of great significance for the extraction and enrichment of LTL from honeysuckle. Results In this system, a novel surface imprinting polymer for luteolin, denoted as Fe3O4@SiO2@MIP, was synthesized using covalent-noncovalent synergistic imprinting strategies. 3-acrylamidephenylboric acid was adopted as covalent functional monomer, deep eutectic solvent (choline chloride/methacrylic acid (ChCl/MAA, 1/2, n/n)) and methacrylic acid as the non-covalent functional monomers, and Fe3O4@SiO2 nanoparticles as the magnetic support. The resultant Fe3O4@SiO2@MIP displayed a uniform morphology, good crystallinity, and excellent magnetic properties. Meanwhile, the binding experiments demonstrated that Fe3O4@SiO2@MIP exhibited high binding performance and the maximum adsorption capacity was 20.97 mg/g. Moreover, the selectivity and reusability behavior of them were satisfactory. In addition, this polymer, serving as an adsorbent, presented practical application potential in separation and enrichment of LTL from honeysuckle. Conclusion The covalent-noncovalent synergistic imprinting strategy could greatly facilitate the preparation of imprinted nanoparticles for the specific recognition of LTL, providing a valuable approach for the enrichment of LTL in complex samples.